End-to-End Implementation of Various Hybrid Neural Networks on a Cross-Paradigm Neuromorphic Chip - Wang, Guanrui; Ma, Songchen; Wu, Yujie; Pei, Jing; Zhao, Rong; Shi, Luping (Frontiers in Neuroscience, 2021)
Integration of computer-science oriented artificial neural networks (ANNs) and neuroscience oriented spiking neural networks (SNNs) has emerged as a highly promising direction to achieve further breakthroughs in artificial intelligence through complementary advantages. This integration needs to support individual modelling of ANNs and SNNs as well as their hybrid modelling, which not only simultaneously calculates single-paradigm networks but also converts their different information representations. It remains challenging to realize effective calculation and signal conversion on the existing dedicated hardware platforms. To solve this problem, we propose an end-to-end mapping framework for implementing various hybrid neural networks on many-core neuromorphic architectures based on the cross-paradigm Tianjic chip. We construct hardware configuration schemes for four typical signal conversions and establish a global timing adjustment mechanism among different heterogeneous modules. Experimental results show that our framework can implement these hybrid models with low execution latency and low power consumption with nearly no accuracy degradation. This work provides a new approach of developing hybrid neural network models for brain-inspired computing chips and further tapping the potential of these models.